Enhanced versus standard fortification of pasteurized donor human milk for growth in very low birth weight infants: a randomized controlled trial - Ong, Chengsi; Wong, Anng Anng; Wong, Siew Tin; Zheng, Ying; Pang, Cynthia Pui Chan; Jayagobi, Pooja Agarwal; Yeo, Joo Guan; Yeo, Kee Thai; Chua, Mei Chien (Frontiers in Nutrition, 2025)
IntroductionVery-low-birthweight (VLBW) infants on pasteurized donor human milk (PDHM) have poorer growth compared to infants on fortified mother's milk, suggesting that standard fortification methods for PDHM are inadequate.MethodsWe designed a randomized controlled trial to determine whether an enhanced method of fortification (EF) improved growth in VLBW infants compared to standard fortification (SF). VLBW infants admitted to our tertiary-level neonatal intensive care unit were randomized to receive a bovine powdered human milk fortifier (HMF) added to PDHM (SF), or specially selected high-fat PDHM (fat concentration ≥3.8 g/dL) with bovine powdered HMF and a liquid protein fortifier providing an additional 0.67 g/dL protein (EF). Primary outcome was impaired weight gain defined as weight z-score drop of ≥0.8 from birth at 37 weeks or hospital discharge, whichever earlier. Secondary outcomes included change in length and head circumference (HC) z-scores from birth, requirement for high calorie formula, and rates of bronchopulmonary dysplasia (BPD) and retinopathy of prematurity (ROP).ResultsA total of 61 infants were randomized (31 SF, 30 EF). Impaired weight gain was not significantly different (SF 83.9% vs. EF 73.3%, p = 0.347), with similar declines in weight z-scores from birth in both groups SF −1.27 [interquartile range (IQR) −1.71, −0.87] vs. EF −1.13 (IQR −1.46, −0.78), p = 0.403. However, the EF group had a smaller decline in length and HC z-scores from birth to discharge compared to the SF group [Length z-score change: −0.92 (IQR −1.64, −0.48) vs. −1.64 (IQR −2.21, −0.89), p = 0.007; HC z-score change: −0.08 (IQR −0.74,0.58) vs. −0.86 (IQR −1.81, −0.21), p = 0.014]. The EF group also required less high calorie formula supplementation [0% (IQR 0-4.1) vs. 3.8% (IQR 0 −16.9), p = 0.032]. Rates of BPD and ROP were not significantly different between groups.ConclusionAmong VLBW infants, EF did not improve weight gain, but reduced declines in HC and linear growth compared to SF.